READING FOR PLEASURE: EXPLORING FEMALE STUDENTS’ MOTIVATION IN READING STORIES - Afnitasari, Dinda; Maharani, Mega Muliyaning (Jurnal Ilmiah Penelitian Mahasiswa, 2024)
Every student has different motivations for reading, specifically male and female students. This study aimed to explore female students’ motivation especially in reading stories. The participants of this study were female students from grades 10th-12th at an Islamic senior high school in Semarang, Central Java, Indonesia. This study used quantitative method in the form of survey research design. The data were collected using MRQ (Motivation for Reading Questionnaire) which contains 8 indicators regarding reading motivation: reading for curiosity, reading for involvement, reading for challenge, reading for recognition, reading for grades, reading for social reading for competition, and reading for compliance. It has 40 items developed from these 8 indicators which was printed out to be shared with the students. The data collected were statistically analyzed by Statistical Package for The Social Sciences (SPSS). The findings of this study reveal that female students of an Islamic senior high school in Semarang were extrinsically motivated to read stories. This is a note that students still need more engagement from the teacher in reading to finally read because of their own will. Keywords: female students, reading for pleasure, reading motivation, story reading